2004
DOI: 10.1111/j.1600-0501.2004.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

rhBMP‐2 significantly enhances guided bone regeneration

Abstract: rhBMP-2/ACS significantly enhances GBR at turned and surface-etched dental implants. The dental implant surface technology does not appear to substantially influence bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
120
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 41 publications
15
120
3
Order By: Relevance
“…This may be attributed to the effects of rhBMP-2 not only on early corticalization of the SM, but also on new bone formation in the peri-implant area. Several studies have found that rhBMP-2 contributed to new bone formation around the implant, thereby supporting the proposal that rhBMP-2 plays such a role [20][21][22]. Therefore, a higher concentration and dosage of rhBMP-2 may be needed in order to achieve results similar to those reported in the previous study.…”
Section: Discussionsupporting
confidence: 62%
“…This may be attributed to the effects of rhBMP-2 not only on early corticalization of the SM, but also on new bone formation in the peri-implant area. Several studies have found that rhBMP-2 contributed to new bone formation around the implant, thereby supporting the proposal that rhBMP-2 plays such a role [20][21][22]. Therefore, a higher concentration and dosage of rhBMP-2 may be needed in order to achieve results similar to those reported in the previous study.…”
Section: Discussionsupporting
confidence: 62%
“…Since periodontal tissue defects typically remain unhealed and often lead to further tissue degeneration and the loss of teeth, understanding the physiological role of these proteins in the wound-healing cascade and tissue regeneration is of critical importance in advancing the treatment of periodontal tissue loss and in enhancing periodontal tissue regeneration. Most of the research in this field has centered on examining the therapeutic effects that these molecules have on hard or soft tissues with the presence of 1 or more growth factors [9][10][11][12][13][14][15][16] . However, as the fields of tissue engineering and biomaterials merge with molecular and cellular biology, new drug delivery vehicles can be utilized to study the in vivo effect of these molecules on periodontal tissue regeneration or periodontal defect repair.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to a sustained delivery profile or a higher stability of the growth factor (103,141). Overall, loading implants with growth factors has shown to accelerate bone formation (129,131,142,143) and to facilitate the bridging of small gaps between implant and surrounding bone (130,144,145). In summary, coating implants with locally acting growth factors can improve the remodelling process at the tissue-implant interface, and is therefore a promising option for establishing an improved integration of implants into healing bone.…”
Section: Growth Factor Immobilizationmentioning
confidence: 99%